Rapid pulsed-field gel electrophoresis protocol for Legionella pneumophila typing (Italian Journal of Public Health, 2008)
Background: Genomic DNA patterns generated by pulsed-field gel electrophoresis (PGFE) are highly specificfor different strains of an organism and have significant value in epidemiologic investigations of infectiousdisease outbreaks. A disadvantage of PFGE is that the procedure requires up to 6 days to complete.Methods: We developed a rapid PFGE protocol for subtyping Legionella pneumophila isolates based on thestandardized protocol currently used. Various combinations of reaction conditions (e.g., lysis time andtemperature, restriction enzyme concentration) and electrophoresis parameters were applied to devise asimple and rapid PFGE protocol that could also be used for frozen bacteria.Results: PFGE analysis of Legionella pneumophila isolates can be completed in 26 hours using this protocolcompared to 6 days for the conventional one.Conclusions: We successfully applied a rapid PFGE protocol for Legionella pneumophila typing andcomparison of the patterns obtained from the rapid compared with the conventional method showed that therapid protocol gave identical and highly reproducible results.
Keywords: legionella pneumophila; molecular typing; PFGE